Evaluation of water security in Kathmandu Valley before and after water transfer from another basin - Thapa, Bhesh Raj; Ishidaira, H.; Pandey, Vishnu Prasad; Bhandari, T.M.; Shakya, N.M. (MDPI, 2018)
Kathmandu Upatyaka Khanepani Limited (KUKL) has planned to harness water from outside the valley from Melamchi as an inter-basin project to supply water inside the ring road (core valley area) of the Kathmandu Valley (KV). The project, called the “Melamchi Water Supply Project (MWSP)”, is expected to have its first phase completed by the end of September 2018 and its second phase completed by the end of 2023 to supply 170 MLD (million liters a day) through the first phase and an additional 340 MLD through the second phase. The area has recently faced a severe water deficit and KUKL’s existing infrastructure has had a limited capability, supplying only 19% of the water that is demanded in its service areas during the dry season and 31% during the wet season. In this context, this study aims to assess the temporal trends and spatial distribution of household water security index (WSI), defined as a ratio of supply to demand for domestic water use for basic human water requirements (50 L per capita per day (lpcd)) and economic growth (135 lpcd) as demand in pre and post-MWSP scenarios. For this purpose, data on water demand and supply with infrastructure were used to map the spatial distribution of WSI and per capita water supply using ArcMap. Results show a severe water insecurity condition in the year 2017 in all KUKL service areas (SAs), which is likely to improve after completion of the MWSP. It is likely that recent distribution network and strategies may lead to inequality in water distribution within the SAs. This can possibly be addressed by expanding existing distribution networks and redistributing potable water, which can serve an additional 1.21 million people in the area. Service providers may have to develop strategies to strengthen a set of measures including improving water supply infrastructures, optimizing water loss, harnessing additional water from hills, and managing water within and outside the KUKL SAs in the long run to cover the entire KV.